[PP.10.08] PRESENCE OF AORTIC ABDOMINAL CALCIFICATIONS IN PATIENTS WITH RESISTANT HYPERTENSION AND BP RESPONSE IN THE RENAL DENERVATION FOR HYPERTENSION (DENERHTN) TRIAL. (September 2016) - Courand, P.-Y.; Pereira, H.; Gosse, P.; Bobrie, G.; Delsart, P.; Mounier-Vehier, C.; Lantelme, P.; Denolle, T.; Dourmap, C.; Halimi, J.–M.; Girerd, X.; Rossignol, P.; et al.
Abstract : Objective: The DENERHTN trial confirmed the BP lowering efficacy of renal denervation (RDN) added to a standardised stepped-care antihypertensive treatment (SSAHT) for resistant hypertension (RH) at 6 months. There was large between-patient variability in the BP response to RDN and SSAHT. The presence of aortic abdominal calcification (AAC), which has been related to arterial stiffness, may impact BP response to both RDN and SSAHT. Design and method: Patients with confirmed RH to 4-week treatment with indapamide 1.5 mg/day, ramipril 10 mg/day (or irbesartan 300 mg/day), and amlodipine 10 mg/day on daytime ABPM (> = 135/85 mmHg) were randomly assigned to RDN+SSAHT, or the same SSAHT alone (control group). After randomisation, spironolactone 25 mg/day, bisoprolol 10 mg/day, prazosin 5 mg/day, and rilmenidine 1 mg/day were sequentially added from months 2 to 5, in both groups if home BP was > = 135/85 mmHg. AAC were delineated blind to the randomization with a semiautomatic segmentation software from the aortic hiatus to the iliac bifurcation on each pre-randomization abdominal CT angiogram. Results: Of the 106 randomised patients, 42/53 in the RDN group and 48/53 in the control group were analyzed because of missing endpoints (age: 54.6+/-10.6 years, males: 61.1%, type 2 diabetes: 22.2%, daytime ambulatory BP: 154/93 mmHg). 78.9% of patients had AAC. Median (IQR) AAC volume was 451 (34–2225) mm3 in all patients. Increasing tertiles of AAC were significantly associated with increasing age, male sex, Caucasian ethnicity, smoking, diabetes, hypercholesterolemia, prior cardiovascular events and obstructive sleep apnea (Table). Higher AAC was associated higher levels of ambulatory and central pulse pressure and pulse wave velocity at baseline. However, at 6-month follow-up, the change in daytime ambulatory SBP/DBP and number of controlled patients did not significantly differ according to tertiles of AAC. Figure. No caption available. Conclusions: In these highly selected patients with RH, AAC were associated with arterial stiffness and cardiovascular risk factors. The presence AAC on CT-angiogram did not impact the BP response in patients treated with RDN+SSAHT or SSAHT alone.